Beberapa Aspek Kenisbian dan Kesamaran Perjanjian Internasional - Sik, Ko Swan (Indonesian Journal of International Law, 2006)
The article does not purport to analyse an international law problem relating to a speific international agreement, nor does it pretend to develop any theoritical paradigm. It merely puts on stage the apparently clear and simple notion of international agreement while at the same time confronting the reader with its essenially relative nature by signalling the many ambiguities and ambivalences hidden behind the term. The author’s sole intention is to invite the reader’s attention to this feature of relativity so as to prevent him from taking the concept of international agreement too easily for granted. The following aspects relating to the concept of international agreement, which could easily be augmented, are successively briefly reviewed; the meaning asigned to the adjective “international”; the legally binding or non-binding character of an international agreement; the agreement’s characterization as a source of rights and duties and its denial, the normative relativity of the rights and duties emanating from the international agreement, the case of “administrative agreements” and the obscrurity as to the identity of its parties under international law. Perjanjian Internasional yang Dibuat oleh Organisasi Internasional by Sri Setianingsih Suwardi: Nowadays, International Organizations has been recognized as one of the international law subject after exceeded a long winding road. The logical consequence of the recognition is the capability of International Organization to construct an international agreement as well as a State has done. Nevertheless, there are still several mechanism differences between State and International Organization in construct an international agreement. The main difference is about who has the authority to make a deal in international agreement process. This article explores and analyzes the great effort of international organization to gain the recognition as one of international law subject, also the authority of international organization related to the construction of international news.